Sustainable competitive advantage of taximonger among taxi companies / Ahmad Fikri Ahmad Yasmin, Mohamad Amirudin Hashim and Mohd Adnan Arshad - Ahmad Yasmin, Ahmad Fikri; Hashim, Mohamad Amirudin; Arshad, Mohd Adnan (2014)
The purpose of this study is to analyze the sustainable competitive advantages among TaxiMonger among taxi companies. This research used one type of data collection method which is primary data. Here, researchers use five independent variables that are web advertisement, customer satisfaction, customer loyalty, service quality and innovation, to identify the factors that influence the sustainable competitive advantage of TaxiMonger Sdn. Bhd among taxi companies. The primary data is collected from commuters who come to Kuala Lumpur, Sentral who has been chosen as the respondents of this research. Journal and any other information gathered from existing data and articles besides collected from the website and other internet sources. The implication of this study can be show on this paper illustrates a powerful, but simple and relatively inexpensive ways to study the sustainable competitive advantage of TaxiMonger among taxi companies. The originality of the major contribution from this study is to alert the competitive advantages of TaxiMonger Sdn. Bhd as the company becomes the first mover in the taxi industry.